200 Years of Caprimulgid Records in Southern Brazil: A Comparison between the Literature and Citizen Science Data - Cavarzere, Vagner [UNESP] (MDPI, 2023)
Although the ornithological history of southern Brazil has been amassed over the last 200 years, few attempts have been made to describe how species have accumulated. Furthermore, the collaboration of citizen scientists has considerably changed the way researchers analyze empirical data. Caprimulgidae (Nightjars and Nighthawks) species were used to illustrate how species have been recorded since the 1800s in Paraná State by comparing traditional and citizen science data. In addition, reports from both researchers and citizen scientists on the breeding biology of these caprimulgids have been verified. A literature review was conducted searching for the Caprimulgid species within the territory of Paraná. Regarding citizen science, records were obtained from four ornithological platforms. Overall, 14 species were detected within the state, 13 of which have been described in the literature, including 1 endemic to the Atlantic Forest and 3 threatened species. Citizen scientists detected all 13 taxa, in addition to one undocumented species that has never been recorded by researchers. There were 12 times more records on ornithological platforms in half of the sampling effort accumulated in studies, but most of them date from the last five years. Citizen scientists also visited 4.5 times more locations than researchers. Citizen scientists accumulated more records around September and November, and most (59%) records were from 2020–2022. Researchers mentioned species as early as 1820, while continuous studies only began during the 1980s; they concentrated their fieldwork mostly in September. Only one (2%) study sought to describe the breeding biology of a caprimulgid species, but there were 84 observations on ornithological platforms between 2004–2022 on their reproduction. Because of the evident mismatch between traditional and citizen science data due to a lack of congruence between their actions, it is suggested that ornithology in Paraná, as well as other Brazilian regions, would benefit the most if traditional and citizen scientists improved their networking communication to focus on common purposes instead of acting independently.
Keywords: Caprimulgidae; literature review; observer behavior; ornithological platforms; Paraná State